Enhancing Higher Education Pedagogy with ChatGPT: Leveraging the Power of Generative AI - Zohaib Hassan Sain; Hasan Baharun; Nurulannisa Binti Abdullah (Journal Emerging Technologies in Education, 2024)
Background. The prevalence of burnout among students at madrasas has reached a critical level, highlighting the need for efficient administration of counselling services to tackle this issue. Understanding how counselling may mitigate student burnout is crucial for improving educational achievements and promoting student welfare. Purpose. This research investigates the efficacy of counselling service administration in mitigating burnout among students in madrasas. The study aims to analyse the effects of these services and provide not just valuable insights, but practical, actionable suggestions for enhancing counselling practices in educational institutions, making the research directly applicable to the field.   Method. This research employs a qualitative approach, using a case study technique to assess the function of counselling services in the school setting. Data were gathered via comprehensive interviews, participatory observations, and documentation studies involving students, counsellors, and instructors. Thematic analysis was used to identify the primary themes that arose from the data. Results. The study results indicate that doing a thorough evaluation of student requirements has a substantial impact on reducing the likelihood of burnout by facilitating the development of more suitable remedies. Appointing qualified counsellors improves the efficacy of counselling services by fostering a more profound comprehension of student concerns. Continuous mentorship programs provide crucial emotional and practical assistance, aiding students in cultivating appropriate coping mechanisms. Moreover, including student input enhances the quality of counselling services.   Conclusion. This research provides a substantial advancement in understanding counselling service administration. It introduces intervention models that may be used in different educational institutions to address student burnout effectively. The results provide pragmatic advice for other academic environments, including strategies to improve their counselling services and effectively tackle student burnout.